Assessing finasteride‐associated sexual dysfunction using the FAERS database. (3rd April 2017) - Gupta, A.K.; Carviel, J.; MacLeod, M.A.; Shear, N.
Abstract: Background: Postmarketing reports suggest that finasteride causes sexual dysfunction despite a low incidence reported in clinical trials. Therefore, the extent of risk remains unknown. Objective: To determine whether the risk of sexual dysfunction is higher among individuals treated with finasteride compared to a baseline risk for all other drugs using the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) database. Methods: A case by non‐case disproportionality approach was used whereby a reporting odds ratio (ROR) with 95% confidence interval (CI) was calculated. The National Ambulatory Medical Care Survey (NAMCS) was used to confirm results. Results: A significant disproportionality in reporting of sexual dysfunction with the use of finasteride was observed whether finasteride was indicated for hair loss (ROR = 138.17, 95% CI: 133.13, 143.4), prostatic hyperplasia (ROR = 93.88, 95% CI: 84.62, 104.16) or any indication (ROR = 173.18, 95% CI: 171.08, 175.31). When these results were stratified by age, disproportionality was strongest at 31–45 years. Conclusion: Use of finasteride has led to an increase in reports of sexual dysfunction where it is believed to be the primary suspect.